Sugar Intake and Cancer: A Literature Review - Nikmah Utami Dewi; Rian Diana (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
ABSTRACTBackground: Cancer is the second leading cause of death after heart disease globally (total death 9.6 million). Cancer prevalence is increasing in Indonesia from 1.4 per 1000 people in 2013 to 1.79 per 1000 people in 2018. Diet is linked with cancer prognosis, particularly carbohydrate intake which stimulates insulin signals that can be potent mitogens.Purpose: This literature review aims to examine sugar intake and cancer incidence.Method: This literature review (traditional review) using the keywords “cancer”,” sugar”, “carbohydrate”, “insulin” and “hyperinsulinemia” in the Sciencedirect database and Google search engine. The inclusion criteria were peer-review articles or documents from credible national and international institutions, the literature uses English or Bahasa (Indonesian Language). The exclusion criteria were that the literature had similar content or redundant with other literature.Result: Sugar increases insulin resistance which enhances the levels of bioactive IGF-I that contribute to raising the risk of cancer. Prolonged hyperinsulinemia reduces the production of growth-promoting factors such as IGFBP-1 and IGFBP-2 which normally bind to and inhibit the action of IGF-I with resultant increases in the levels of free, bio-active IGF-I, and concomitant changes in the cellular environment that favor cancer development, proliferation, and metastatic cancer cells.Conclusion: The mechanism of insulin and IGF-1 stimulate and accelerate cancer cell proliferation may explain the relationship between sugar intake and cancer incidence. Adopting a balanced diet, changing or decreasing sugar intake with healthier food coupled with increased physical activity reduces the risk of cancer.